The experience of caring for patients with dementia within a general hospital setting: a meta-synthesis of the qualitative literature. (2nd January 2017) - Turner, Alex; Eccles, Fiona J.R.; Elvish, Ruth; Simpson, Jane; Keady, John
Abstract: Objectives: The optimal care of people with dementia in general hospitals has become a policy and practice imperative over recent years. However, despite this emphasis, the everyday experience of staff caring for this patient group is poorly understood. This review aimed to synthesise the findings from recent qualitative studies in this topic published prior to January 2014 to develop knowledge and provide a framework to help inform future training needs. Method: A systematic search of the literature was conducted across five academic databases and inclusion/exclusion criteria applied to the retrieved papers. A meta-ethnographic approach was utilised to synthesise the resulting 14 qualitative papers. Results: Five key themes were constructed from the findings: overcoming uncertainty in care; constraints of the environmental and wider organisational context; inequality of care; recognising the benefits of person-centred care; and identifying the need for training. These themes explore the opportunities and challenges associated with caring for this group of patients, as well as suggestions to improve staff experiences and patient care. Conclusion: The synthesis highlighted a lack of knowledge and understanding of dementia within general hospital staff, particularly with regard to communication with patients and managing behaviours that are considered challenging. This limited understanding, coupled with organisational constraints on a busy hospital ward, contributed to low staff confidence, negative attitudes towards patients with dementia and an inability to provide person-centred care. The benefits of dementia training for both ward staff and hospital management and peer discussion/support for ward staff are discussed.